The Use of Metaphors in the Album Poems, Prayers and Promises by John Denver - Karundeng, Luis Vigo Berny; Lotulung , Donald Ringgo; Sebayang, F. Ari Anggraini (Universitas Sam Ratulangi, 2026)
This research, entitled “The Use of Metaphors in Album Poems, Prayers and Promises by John Denver” aims to identify, classify, and analysis the metaphorical expressions embedded in the lyrics. Guided by Lakoff and Johnson’s (1980) conceptual metaphor theory—structural, orientational, and ontological metaphors—the research adopts a descriptive qualitative approach, using twelve songs from the album as primary data. The findings reveal a consistent and meaningful application of metaphorical language that transforms abstract ideas including time, memory, and emotion into more tangible concepts, enhancing lyrical depth and emotional resonance. The study concludes that metaphor in Denver’s songwriting is not merely decorative but serves as a cognitive tool that shapes understanding and strengthens the connection between artistic expression and human experience, thereby contributing to broader discussions in semantic and cognitive linguistic research.